A concise history of modern India - Metcalf, Barbara Daly.; Metcalf, Thomas R. (New York : Cambridge University Press, 2012)
"A Concise History of Modern India, by Barbara D. Metcalf and Thomas R. Metcalf, has become a classic in the field since it was first published in 2001. As a fresh interpretation of Indian history from the Mughals to the present, it has informed students across the world. In the third edition of the book, a final chapter charts the dramatic developments of the last twenty years, from 1990 through the Congress electoral victory of 2009, to the rise of the Indian high-tech industry in a country still troubled by poverty and political unrest. The narrative focuses on the fundamentally political theme of the imaginative and institutional structures that have successively sustained and transformed India, first under British colonial rule and then, after 1947, as an independent country. Woven into the larger political narrative is an account of India's social and economic development, and its rich cultural life. Throughout, the authors argue that despite a powerful historiographical tradition to the contrary, no enduring meaning can be given to categories such as 'caste', 'Hindu', 'Muslim', or even 'India'"--
"This is a concise history of India since the time of the Mughals. It comprises the history of what was known as British India from the late eighteenth century until 1947, when the subcontinent was split into the two independent countries of India and Pakistan, and of the Republic of India thereafter. (The history of Pakistan, and after 1971, of Bangladesh, is taken up in a separate volume in this series.) In this work we hope to capture something of the excitement that has characterized the field of India studies in recent decades. Any history written today differs markedly from that of the late 1950s and early 1960s when we, as graduate students, first 'discovered' India. The history of India, like histories everywhere, is now at its best written as a more inclusive story, and one with fewer determining narratives. Not only do historians seek to include more of the population in their histories - women, minorities, the dispossessed - but they are also interested in alternative historical narratives, those shaped by distinctive cosmologies or by local experiences. Historians question, above all, the historical narratives that were forged - as they were everywhere in the modern world - by the compelling visions of nationalism"--
Includes bibliographical references and index.
Keywords: India -- History